Considerations on the radio emission from extended air showers. Issue 5 (19th May 2016) - Conti, E.; Sartori, G.
Abstract: The process of radio emission from extended air showers produced by high energy cosmic rays has reached a good level of comprehension and prediction. It has a coherent nature, so the emitted power scales quadratically with the energy of the primary particle. Recently, a laboratory measurement has revealed that an incoherent radiation mechanism exists, namely, the bremsstrahlung emission. In this paper we expound why bremsstrahlung radiation, that should be present in showers produced by ultra high energy cosmic rays, has escaped detection so far, and why, on the other side, it could be exploited, in the 1–10 GHz frequency range, to detect astronomical γ -rays. We propose an experimental scheme to verify such hypothesis, which, if correct, would deeply impact on the observational γ -ray astronomy.